Association Between Tumor Progression Endpoints and Overall Survival in Patients with Advanced Neuroendocrine Tumors. (18th September 2017) - Ter‐Minassian, Monica; Zhang, Sui; Brooks, Nichole V.; Brais, Lauren K.; Chan, Jennifer A.; Christiani, David C.; Lin, Xihong; Gabriel, Sylvie; Dinet, Jérôme; Kulke, Matthew H.
Abstract : : Endpoints related to tumor progression are commonly used in clinical trials of novel therapeutic agents for neuroendocrine tumors (NETs). Whether improved tumor control translates into improved overall survival (OS), however, is uncertain. We assessed associations between tumor progression endpoints and OS in observational cohorts of patients with advanced neuroendocrine tumors treated with somatostatin analogs or with everolimus. We identified 440 patients with advanced NET who had received treatment with single‐agent somatostatin analogs and 109 patients treated with everolimus, all of whom were treated at our institution and were evaluable for both tumor progression and survival. We assessed associations between progression‐free survival (PFS) and OS by using the Kendall tau test, and we assessed associations between tumor progression and OS by using a landmark analysis. In the 440 patients treated with somatostatin analogs, we observed a significant correlation between PFS and OS by using the Kendall tau test (0.31; p  < .0001). Additionally, the development of progressive disease was associated with OS in a landmark analysis, at landmark times of 6, 12, 18, and 24 months. In the 109 patients treated with everolimus, we similarly observed a significant correlation between PFS and OS by using the Kendall tau test (0.44; p  < .0001) and associations between progressive disease and OS by using a landmark analysis at 3, 6, and 12 months. In these observational cohorts of patients with metastatic NET treated with single‐agent somatostatin analogs or everolimus, longer times to disease progression and longer PFS were both associated with improved OS. Our findings support the continued use of disease progression endpoints in NET clinical trials. Abstract : In observational cohorts of patients with metastatic neuroendocrine tumor (NET) treated with single‐agent somatostatin analogs or everolimus, longer times to disease progression and longer progression‐free survival were both associated with improved overall survival. These findings support the continued use of disease progression endpoints in NET clinical trials.